2012
DOI: 10.1038/emboj.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

miR-493 induction during carcinogenesis blocks metastatic settlement of colon cancer cells in liver

Abstract: Liver metastasis is a major lethal complication associated with colon cancer, and post-intravasation steps of the metastasis are important for its clinical intervention. In order to identify inhibitory microRNAs (miRNAs) for these steps, we performed 'dropout' screens of a miRNA library in a mouse model of liver metastasis. Functional analyses showed that miR-493 and to a lesser extent miR-493(*) were capable of inhibiting liver metastasis. miR-493 inhibited retention of metastasized cells in liver parenchyma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 43 publications
4
74
0
Order By: Relevance
“…miR-199a targeted the glycosylation enzyme ST6GAL1, reduced the sialylation of Necl-2, indirectly reduced the protein level of Necl-2, and enhanced ErbB2/ErbB3 signaling (32). It was reported that miR-493 inhibited the formation of metastatic foci and thus prevented liver metastasis of colon cancer cells (33). miR-493, was found to be reduced in lung cancer cells and tissues and to suppress cell invasion and proliferation by blocking E2F1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…miR-199a targeted the glycosylation enzyme ST6GAL1, reduced the sialylation of Necl-2, indirectly reduced the protein level of Necl-2, and enhanced ErbB2/ErbB3 signaling (32). It was reported that miR-493 inhibited the formation of metastatic foci and thus prevented liver metastasis of colon cancer cells (33). miR-493, was found to be reduced in lung cancer cells and tissues and to suppress cell invasion and proliferation by blocking E2F1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high levels of miR-493 and miR-493(*), but not pri-miR-493, in primary colon cancer were inversely related to the presence of liver metastasis, and attributed to an increase of miR-493 expression during carcinogenesis [112].…”
Section: Mirnas and Metastasismentioning
confidence: 99%
“…Microarray analyses were performed using Agilent Whole Human Genome 8 Â 60 K Oligo microarrays (24). Microarray data were accessible through Gene Expression Omnibus database (accession number GSE64999).…”
Section: Gene Set Enrichment Analysesmentioning
confidence: 99%